The application of shura in Malaysian Islamic social finance agenda - Abd Rahman, Nurulhuda; Osman, Muhammad Rahimi; Mohd Kharudin, Khairul Ayuni (2023)
This paper highlights the fundamentals and significance of the principle of shura in the collaboration process between Islamic social finance key players in achieving a successful Islamic social finance agenda. This study employs a qualitative approach via library research to obtain relevant data from selected databases, researchers, religious sources, books, reports, and electronic sources. An insight into the relevance of shura in facing challenges scaling the Islamic social finance agenda. The application of shura should be manifested in the development of the Islamic social finance agenda to achieve successful collaboration between Islamic social finance key players. An insight into the importance, challenges, and recommendations to achieve effective shura must be provided, shared, and applied by the relevant parties involved in the Islamic social finance agenda. Effective shura application may lead to successful and beneficial collaboration between the stakeholders of the Islamic social finance agenda. More beneficial models and strategic action can be taken to protect the maslahah or public interest. This study recommends further investigation on the measurement items of the practices of shura in Islamic social finance agenda to acquire in-depth knowledge and a better understanding of the achievement of maqasid al Shariah.